(In)Tolerancia - Martínez Muñoz, Juan Antonio (Anuario de Derechos Humanos. Nueva Época, 2010)
A new interpretation of the meaning and scope of tolerance is presented in this paper, far from common use of the concept and showing historical and current implications. Characterized as an ideological weapon of relativism, raises its use for power to erode the social institutions built by the traditional European culture and to consolidate resulting power interests without being interfered by legal or moral ideas in terms of legitimacy.